2006
DOI: 10.1177/154405910608501004
|View full text |Cite
|
Sign up to set email alerts
|

Origin, Splicing, and Expression of Rodent Amelogenin Exon 8

Abstract: Amelogenin RNA transcripts undergo extensive alternative splicing, and MMP-20 processes the isoforms following their secretion. Since amelogenins have been ascribed cell-signaling activities, we asked if a lack of proteolytic processing by MMP-20 affects amelogenin signaling and consequently alters amelogenin splice site selection. RT-PCR analyses of amelogenin mRNA between control and Mmp20 -/-mice revealed no differences in the splicing pattern. We characterized 3 previously unidentified amelogenin alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…This is necessary as there are at least 15 alternative splice products in WT mice (Hu et al, 1997; Li et al, 2006; Bartlett et al, 2006). Western blots of TgCTRNCKO molars from male offspring indicated that all mouse lines expressed TgCTRNC amelogenin; an example is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is necessary as there are at least 15 alternative splice products in WT mice (Hu et al, 1997; Li et al, 2006; Bartlett et al, 2006). Western blots of TgCTRNCKO molars from male offspring indicated that all mouse lines expressed TgCTRNC amelogenin; an example is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The renamed exon 3 containing the start codon in X. tropicalis corresponded to the known exon 2 in amelogenin of other animals, and renamed exons 4, 6, 7 and 8 in X. tropicalis corresponded to known exons 3, 5, 6, and 7 in other animals. Hence, amelogenin mRNA in X. tropicalis consists of eight exons, although in many other animals it consists of seven exons, except for in mice where exons 8 and 9 which follow exon 7 contain stop codons 17,18) . So-callled exon 4 exists only in some mammals 19) , which also lacks in X. tropicalis.…”
Section: Discussionmentioning
confidence: 99%
“…It was believed that the translocation of the gDNA region containing exons 4 and 5 downstream of exon 7 has triggered the activation of a downstream sequence, resulting in the expression of exon 9 (Bartlett et al, 2006). Here, we show that the exon 9 sequence was recruited long before rodent differentiation, in a placental mammal ancestor, 176-104 Ma ago.…”
Section: Exonmentioning
confidence: 90%